UPAYA INDONESIA MEMBEBASKAN TENAGA KERJA INDONESIA TERPIDANA HUKUMAN MATI DI ARAB SAUDI (2011-2013) - Insani, Fitri; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes about effort of Indonesia to acquitted Indonesia labours who get death penalty in Saudi Arabia’s (2011-2013). There are some Indonesian labours that have been accused of committing a crime that drags them become a convict of the death penalty by a court of Saudi Arabia’s. There are three kind of the death penalty in Saudi Arabia’s, they are: Qishas, Rajam and Ta’zir. As for the allegations imposed on Indonesian labours that under sentence of death in Saudi Arabia’s are torture, murder, perform of magic and adultery.This research used the theory of diplomacy. As for the kind of diplomacy that used are bilateral diplomacy. Bilateral diplomacy is diplomacy carried out by between two countries. This research used nation-state analysis.This study applies qualitative research method with library. The data sources are from books, journal, and the internet.Finnaly, Indonesian government’s actions in providing protection for Indonesian labours who became convicted of the death penalty in 2011-2013 is considered to be the maximum. As for the efforts that has been made are: do moratorium policy, bilateral diplomacy, forming a special task force, appoint of retainer lawyer and assist in paying (diyat) to the families of victims. Those efforts can help the Indonesian labours who convicted of death penalty and get a lighter punishment like a forgiveness from the victim’s family or pay a fine.Keywords: Bilateral Diplomacy, Death Penalty, Effort, Indonesian Labours